The Duke's forbidden ward - Adams, Millie (Harlequin historicals., 2022)
Her unattainable guardian. The man she secretly yearns for! This season, Eleanor Jennings must find a husband. Her guardian, Hugh, the autocratic and devastatingly alluring Duke of Kendal, has made that abundantly clear. The only flaw in his plan? Eleanor's scandalous longing for him! Hugh might consider her off-limits and dangerously innocent, but Eleanor can see the pain and secrets he hides. Can Eleanor also be brave enough to make Hugh see the passion that exists between them?